Sustainable Formulation of Phenol-Based Disinfectants for Industrial and Domestic Use - Iheanocho prosper; Nnadikwe Johnson; Chinemerem Joy Johnson (Journal Majelis Paspama, 2025)
The formulation of effective and sustainable disinfectants is crucial for preventing the transmission of diseases and ensuring public health. This study focuses on the development of a phenol-based disinfectant formulation, with a specific emphasis on sustainability and efficacy. The formulation process involved mixing texapon, pine oil, phenol, chloroxylenol, isopropyl alcohol, and water in specific proportions, while varying the quantities of chloroxylenol (250g, 500g, 1000g, 1500g, and 2000g) and maintaining the quantities of water and isopropyl alcohol constant. The physical properties of the finished product, including pH, relative density, odour, and dispersion in water, were evaluated through comprehensive physical analysis. The study's findings provide valuable insights into the development of effective and sustainable disinfectant formulations, with potential applications in industrial, domestic, and healthcare settings. The research aims to contribute to the advancement of disinfectant technology, promoting public health and safety through the creation of efficacious and environmentally friendly disinfectant products.